(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In the globalized world of healthcare, effective communication between medical professionals, patients, and researchers is essential. As English continues to serve as the dominant language in scientific research, clinical practice, and international collaboration, proficiency in Medical English has become a critical skill for healthcare professionals. This article explores the role of Medical English in modern healthcare, emphasizing its importance in clinical settings, medical education, research, and global healthcare initiatives. The challenges faced by non-native English speakers and strategies for improving Medical English proficiency are also discussed.